Hematological and histo-architectural damages in the kidney and liver of Nile tilapia on exposure to kinalux (Progressive Agriculture, 2015)
Study was conducted to assess the histo-architectural damages of kidney and liver and hematological parameters in Nile tilapia (Oreochromis niloticus) after sub-lethal exposure to kinalux. Fish was exposed to two sub-lethal concentrations (10% and 50%, 0.052 and 0.259ppm of median lethal concentration, respectively) of kinalux for 90 days and a parallel control was run simultaneously. Kidney and liver of exposed individuals exhibited some remarkable changes in their histology in comparison to control. Significant changes also occurred in the number of red blood cell (RBC) and white blood cell (WBC). Duration of exposure appears to have a profound effect on kidney and liver as with increasing duration of exposure histo-architectural damages become more severe.Progressive Agriculture 26 (2): 173-178, 2015